2023
DOI: 10.1080/00224499.2023.2175191
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ginger on Disgust, Sexual Arousal, and Sexual Engagement: A Placebo-Controlled Experiment

Abstract: Sexual problems are common complaints across countries and cultures, and behavioral immune system theory suggests disgust plays an essential role in sexual functioning. The current study investigated 1) if disgust induced by sexual body fluids would reduce sexual arousal, reduce the likelihood of sexual engagement, and enhance disgust toward subsequent erotic stimuli, and 2) if the administration of ginger would affect these reactions. We administered either ginger or placebo pills to a sample of 247 participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 71 publications
2
4
0
Order By: Relevance
“…However, our findings revealed that Z consumption showed no significant relationship with feelings of disgust during sexual behaviors. This finding is partly in line with the study conducted by Wen et al in which it was found that temporary Z consumption (1.5 g) could not suppress feelings of disgust induced by sexual body fluids but did alleviate the suppressing effects of disgust on sexual arousal in women [26].…”
Section: Potential Pathways Behind Association Between Z Consumption ...supporting
confidence: 91%
See 3 more Smart Citations
“…However, our findings revealed that Z consumption showed no significant relationship with feelings of disgust during sexual behaviors. This finding is partly in line with the study conducted by Wen et al in which it was found that temporary Z consumption (1.5 g) could not suppress feelings of disgust induced by sexual body fluids but did alleviate the suppressing effects of disgust on sexual arousal in women [26].…”
Section: Potential Pathways Behind Association Between Z Consumption ...supporting
confidence: 91%
“…Previous studies have shown that long-term use of Z can enhance psychological sexual arousal and desire in women as well as physical erectile function in men [22,23]. Moreover, temporary consumption of 1.5 g of Z has been found to increase feelings of sexual arousal in response to erotic stimuli [26]. Consistent with these findings, the present study suggests that Z consumption is associated with higher levels of sexual desire and arousal during sexual behavior, and then these factors mediate the relationship between Z consumption and sexual behaviors.…”
Section: Potential Pathways Behind Association Between Z Consumption ...mentioning
confidence: 98%
See 2 more Smart Citations
“…Sexual body fluid and neutral fluid tasks . Eight 30-second videos depicting research assistants completing sex-related behavioral approach tasks were used to induce feelings of disgust related to sexual body fluids (also see Wen et al, 2023) [ 42 ]. Four kinds of sexual body fluids including sweat (sweat from the head and neck), saliva, body odor (sweat from an armpit), and genital secretions (semen for female participants and vaginal secretions for male participants) were used.…”
Section: Methodsmentioning
confidence: 99%